Field Emission Behaviour of the Single Wall Carbon Nanotubes Grown by Plasma Enhanced Chemical Vapour Deposition (PECVD) System - Avshish Kumar; Shama Parveen; Samina Husain; Javid Ali; Harsh; M. Husain (Журнал нано- та електронної фізики)
Single wall carbon nanotubes have been grown on Fe using Plasma Enhanced Chemical Vapour Deposition (PECVD) system. The thickness of the Fe film prepared by RF sputtering system was about 10 nm. The field emission characteristic was measured which showed good enhancement factor. The grown CNTs were characterized by various techniques such as SEM, Raman study etc.